2021
DOI: 10.1155/2021/9998176
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of COVID-19 Vaccination among Health Care Workers in Ghana

Abstract: Because health care workers are a reliable source of health information, their acceptance or rejection of COVID-19 vaccines can influence the general population's uptake of COVID-19 vaccines. In this study, we sought to determine the acceptability of COVID-19 vaccines among health care workers in Ghana. Using a cross-sectional design, we collected data from 234 health care workers through a self-administered online survey from 16 January to 15 February 2021. Descriptive, bivariate, and multivariate analyses we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
116
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 23 publications
(19 reference statements)
13
116
4
1
Order By: Relevance
“…signi cant difference among different age groups(Qattan et al 2021). The same ndings were reported by two similar studies conducted in Egypt and Ghana(Fares et al 202 ;Agyekum et al 2021). …”
supporting
confidence: 87%
See 1 more Smart Citation
“…signi cant difference among different age groups(Qattan et al 2021). The same ndings were reported by two similar studies conducted in Egypt and Ghana(Fares et al 202 ;Agyekum et al 2021). …”
supporting
confidence: 87%
“…However, in Ghana, Agyekum et al, found that39.3%of HCWs accepted to get the COVID-19 vaccines while more than half of them indicated non-acceptance (Agyekum et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Males are more likely than females to accept COVID-19 vaccines, according to other observational studies. 26,32,33 The educational level was also a significant factor in COVID-19 vaccine acceptance. Participants with a college diploma or higher were more likely to accept the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…26,[32][33][34][35][36] In a report in Ghana, for example, insufficient evidence about the vaccine's safety and vaccine side effects were the key reasons for people refusing to accept COVID-19 vaccines. 26 The limitation of this study is that it is cross-sectional in nature, making it difficult to draw long-term conclusions. The results of this research were solely based on quantitative techniques, with no other tools such as focus group discussions or in-depth interviews being used to supplement the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Hence there is a need to get the populace immunized. 3 Vaccination is an effective method of combating infectious diseases by training the immune system to recognize and combat pathogens, either viruses or bacteria. 4 Pharmaceutical companies and researchers around the world have collaborated to develop safe and effective vaccines.…”
Section: Introductionmentioning
confidence: 99%